Servo pattern enhancements for high areal density hard disk drives - Ma, Kun (2017)
The growth of areal density (AD) in hard disk drive (HDD), which measures the data bits per unit area, has slowed down considerably in recent years from the average of 30% annual increase rate achieved in past decades. The main reason is that the current perpendicular magnetic recording (PMR) technology has reached its bottleneck of the so-called superparamagnetism. In the meantime, HDD is facing a strong competition and high market share challenge from solid state drive (SSD). As a result, HDD industry is striving to improve the AD with some new technologies. Heat-assisted magnetic recording (HAMR) is the most viable and promising technology to bring the AD beyond a few terabyte per square inch in the coming decade. When the AD is bigger than one terabyte per square inch, the track width is expected to be smaller than a few tens of nanometers. Being a mechanical device, ever decreasing track width has imposed more stringent requirements on the servo system for the better track-following performance of read and write operations.